2008
DOI: 10.1002/9780470151808.sc01c05s4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Autogenic Human Feeder Cells for Growth of Human Embryonic Stem Cells

Abstract: Human embryonic stem cells (hESCs) that are currently distributed under NIH guidelines, as well as many of those that are not on the NIH registry, have been derived and maintained in coculture with growth‐arrested mouse embryonic fibroblasts (MEFs). Using this mouse support system may compromise the therapeutic potential of these hESCs because of the risk of transmitting xenopathogens. Alternatively, to reduce this risk, methods to culture undifferentiated hESCs on autologous hESC‐derived human feeder layers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Since the initially high activin A production decreased much more slowly and was maintained on a higher level compared to the other bioreactors, the results from gene expression analysis and from histological studies suggest that differentiation in this reactor was suppressed by a ‘feeder cell‐like’ activity. This could be due to differentiation of some hESCs into fibroblasts or fibroblast‐like cells with the ability to secrete activin A, and that are able to support the self‐renewal of undifferentiated hESCs, as has been described in 2D cultures in the literature (Xu et al ., ; Stojkovic et al ., ; Yoo et al ., ; Gonzalez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the initially high activin A production decreased much more slowly and was maintained on a higher level compared to the other bioreactors, the results from gene expression analysis and from histological studies suggest that differentiation in this reactor was suppressed by a ‘feeder cell‐like’ activity. This could be due to differentiation of some hESCs into fibroblasts or fibroblast‐like cells with the ability to secrete activin A, and that are able to support the self‐renewal of undifferentiated hESCs, as has been described in 2D cultures in the literature (Xu et al ., ; Stojkovic et al ., ; Yoo et al ., ; Gonzalez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…A possible explanation for the origin of this ‘feeder cell‐like’ activity is that, under the influence of the culture medium used, some of the hESCs differentiated into cells exhibiting self‐renewal supportive activity. This is in accordance with studies by other groups that showed that autologous hESC‐derived feeder cells are able to support the self‐renewal of undifferentiated hESCs (Xu et al ., ; Stojkovic et al ., ; Yoo et al ., ; Gonzalez et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…hESC-derived fibroblasts were generated as described [14] for use in global gene expression comparisons. These fibroblasts were grown in DMEM+10% FBS at 37°C/5% CO 2 and fed on alternate days and passaged weekly with 0.05% trypsin (Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…They were harvested at passage 41. hESC-derived fibroblasts (hESC-Fibro) were derived as a stable proliferating population from spontaneously differentiating passage 40 WA09 hESC cells (Gonzalez et al 2008); after their differentiation they were expanded in two batches, to passage 11 and passage 13 before harvesting. The neonatal fibroblast line (Fibro) cell line was obtained from GlobalStem, Inc (newborn human foreskin fibroblasts, untreated) and was harvested for analysis at passage 13.…”
Section: Cell Culture and Dna Preparationmentioning
confidence: 99%